Change Is Hard: Individual Differences in Children's Lexical Processing and Executive Functions after a Shift in Dimensions. Issue 2 (3rd April 2022) - Pomper, Ron; Kaushanskaya, Margarita; Saffran, Jenny
ABSTRACT: Language comprehension involves cognitive abilities that are specific to language as well as cognitive abilities that are more general and involved in a wide range of behaviors. One set of domain-general abilities that support language comprehension are executive functions (EFs), also known as cognitive control. A diverse body of research has demonstrated that EFs support language comprehension when there is conflict between competing, incompatible interpretations of temporarily ambiguous words or phrases. By engaging EFs, children and adults are able to select or bias their attention toward the correct interpretation. However, the degree to which language processing engages EFs in the absence of ambiguity is poorly understood. In the current experiment, we tested whether EFs may be engaged when comprehending speech that does not elicit conflicting interpretations. Different components of EFs were measured using several behavioral tasks and language comprehension was measured using an eye-tracking procedure. Five-year-old children (n = 56) saw pictures of familiar objects and heard sentences identifying the objects using either their names or colors. After a series of objects were identified using one dimension, children were significantly less accurate in fixating target objects that were identified using a second dimension. Further results reveal that this decrease in accuracy does not occur because children struggle to shift between dimensions, but rather because they are unable to predict which dimension will be used. These effects of predictability are related to individual differences in children's EFs. Taken together, these findings suggest that EFs may be more broadly involved when children comprehend language, even in instances that do not require conflict resolution.